Моральні основи сучасного українського законодавства - Припхан, І.І. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
В статье анализируются нормы Конституции Украины, гражданского, семейного, трудового и криминального права на предмет их соответствия моральным основам общества. The article examines the norms of the Constitution, Civil, pamily Labor and Criminal law for their compliance with the moral principles of society. Moral orientation of the existing legislation is thought of.